STUDI FENOMENOLOGI PENGGUNA INSTAGRAM DENGAN ZERO POST PADA FEED DI KALANGAN MAHASISWA UNIVERSITAS MUHAMMADIYAH CIREBON - Risnawati, Ririn; Faridah, Nida; Riaeni, Ida (JIKE: Jurnal Ilmu Komunikasi Efek, 2024)
The research conducted by this researcher aims to find out and explain the motives of Instagram users with zero posts on feeds among students of the University of Muhammadiyah Cirebon. Every social media user, especially Instagram users with zero posts on the feed certainly have certain motives that are the cause and purpose for someone to act. In this study, researchers used qualitative methods with phenomenological studies using phenomenological theory according to the views of Alfred Schutz. Using this theory, because in this study want to know someone's experience that is the cause and purpose so that Instagram users choose zero posts on the feed. Alfred Schutz's theory of approach classifies motives in two parts, namely: 1) The Motive of Cause (Because of Motive) which refers to past experiences that are the reason or driver and 2) the Motive of Purpose (in Order to Motive) which refers to goals and expectations to be achieved in the future. The results of this study show that based on the Motive of Cause (Because of Motive), there are four motives that are the reasons for the aesthetic standard motive, the motive for being affected by bullying, the motive for worrying about photo abuse, and the motive for being affected by sexual harassment. Based on the Motive of Purpose (in Order to Motive) there are three motives that become the goal, namely the motive of comfort in using Instagram, the motive of being free from negative opinions and unrecognized followers, and the motive of belief in 'ain disease. Regarding the meaning of being an Instagram user zero post on the feed, the results show different meanings that are recognized by some informants, namely Instagram users who are expressive in expressing their feelings, Instagram users who are closed to their personal problems, passive Instagram users, and Instagram hobbies users. Keywords: Motive, Meaning, Instagram, Zero Post